Online distance learning and teaching during COVID-19 / Dr Kuan Woei Keong and Assoc. Prof. Dr Tey Li Sian - Kuan, Woei Keong; Tey, Li Sian (Unit Penerbitan FKAPP, 2020)
Implementation of online teaching has started in our faculty since the movement control order (MCO) was announced in Mar 2020. Before the COVID 19, there was already adoption of virtual education environments in our university. Our lecturers have attempted to conduct lecture through online lessons despite the routine lecture in the physical classroom during the campaign “Week without Wall” in every semester since 2018. This initiative has helped to prepare our lecturers to adapt to the development of teaching and learning technology in this 21st century. Other than the ‘uFuture ’, an official online learning portal developed by UiTM, our staff are also encouraged to utilise third party platform as tools for teaching and learning. The third-party platforms used to conduct the online distance learning in our faculty include Google and Microsoft platforms. Both platforms have provided useful tools in aiding the teaching and learning activities. The implementation of online learning and teaching can be easily achieved through the online platforms. Classes can be organised and managed using either the platform of Microsoft Teams or Google Classroom. Lecturers are allowed to upload their lecture notes/slides prior to the online virtual class. The platforms also provide the statistic of the students’ participation and attendance during the virtual class. In the circumstances when some students are having unstable internet access to participate in the virtual class, pre-recorded lectures or recorded class video can be shared and uploaded. Both platforms are also providing tools to assign tasks and conduct tests among the students.